Application of IFRS 9 Financial Instruments and the Exposure to Credit Risk (Case Study in Ecuador) - Marlon Manya; Miryam C. González-Rabanal (Yayasan Ilomata, 2023)
The COVID-19 pandemic has caused certain elements of the Financial Statements, such as accounts receivable, to show a greater indication of impairment, caused by the difficulty and possibility of insolvency of customers in the recovery of outstanding securities . This caused companies in general to modify the accounting treatment under the international standard IFRS 9 applicable from 2018. The objective of this article is to determine the portfolio risk that affects the calculation of these provisions, through a case study in Ecuador. To this end, a database of clients of a non-financial company was analyzed, and the composition of its portfolio segmented by day of delay, observing the component called probability of default (PD), which was determined by binary logistic regression. A model was obtained that allowed to obtain the desired probability, and consequently under the approach of IFRS 9, the calculation of the expected credit loss (ECL). The results obtained estimated a portfolio impairment of 23%, compared to the baseline scenario of 9%.